2010
DOI: 10.1007/s11259-010-9382-5
|View full text |Cite
|
Sign up to set email alerts
|

Dimensional analysis of milk fat globules in sow milk: effects of the lactation stage and fat content and comparison with vaccine milk

Abstract: To assess the differences in the granulometry of milk fat globules between swine and bovine species, milk samples from 30 lactating sows were analyzed for fat globule dimensions and compared with cow milk samples. Results showed differences between the fat globules: sow milk presents reduced globule diameters compared with cow milk (volume-weighted diameter 2.62 vs. 3.27 µm, p<0.001) and reduced interglobular distance. A positive relationship was observed between milk fat content and globule diameter, while a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…They are composed of a triglyceride core and are surrounded by a natural biological membrane (Fauquant et al, 2005). Faustini et al (2010) concluded that MFG diameter increases with milk fat content, whereas an inverse relationship, although not significant, was observed between globular diameter and lactation day. Wiking et al (2003) reported that the MFG in milk had a high level of fat with a large average diameter.…”
Section: Distribution Of Milk Fat Globule Sizementioning
confidence: 99%
See 2 more Smart Citations
“…They are composed of a triglyceride core and are surrounded by a natural biological membrane (Fauquant et al, 2005). Faustini et al (2010) concluded that MFG diameter increases with milk fat content, whereas an inverse relationship, although not significant, was observed between globular diameter and lactation day. Wiking et al (2003) reported that the MFG in milk had a high level of fat with a large average diameter.…”
Section: Distribution Of Milk Fat Globule Sizementioning
confidence: 99%
“…Little research has studied the effects of SSL on MFG size and the composition of sow milk. In sow milk, MFG are differently dispersed with reduced diameters, which offers a greater attack surface compared to bovine milk (Faustini et al, 2010). They are composed of a triglyceride core and are surrounded by a natural biological membrane (Fauquant et al, 2005).…”
Section: Distribution Of Milk Fat Globule Sizementioning
confidence: 99%
See 1 more Smart Citation
“…The main propose of robust regression is to provide resistant (stable) results in the presence of outliers (Chen, 2002). Applications of robust regression methods in animal researches began to increase with the availability of related computer packages (Çankaya et al, 2006;Çankaya, 2009;Faustini et al, 2010;Yadav et al, 2011). To our knowledge, there is incomplete knowledge on comparative studies of LS and robust regression methods for different sample size and on comparison of estimation methods for parameters of regression model in animal science.…”
Section: Introductionmentioning
confidence: 99%